2010
DOI: 10.4067/s0718-95162010000200007
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulation of Agricultural Biobeds With NPK Fertilizer on Chlorpyrifos Degradation to Avoid Soil and Water Contamination

Abstract: Degradation of the insecticide chlorpyrifos (160 a.i mg kg -1 ) using a biomix of a biobed system biostimulated with inorganic fertilizer (NPK) was investigated. Three concentrations of the fertilizer (0.1%, 0.5% and 1.0% ww -1 ) were evaluated on chlorpyrifos degradation, TCP (3, 5, 6-trichloro-2-pyrinidol) accumulation and biological activity of the biomix. The chlorpyrifos was dissipated efficiently (>75%) after 40 days of incubation and no additional dissipation was obtained with increasing concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…Tortella et al (2010) have recommended biobeds constructed with biomix prepared with Andisol soil and biostimulated with NPK nutrient as a viable alternative of chlorpyrifos dissipation avoiding soil and water contamination. Recently, our study using microbial consortium consisting of Klebsiella sp.…”
Section: Biodegradationmentioning
confidence: 99%
“…Tortella et al (2010) have recommended biobeds constructed with biomix prepared with Andisol soil and biostimulated with NPK nutrient as a viable alternative of chlorpyrifos dissipation avoiding soil and water contamination. Recently, our study using microbial consortium consisting of Klebsiella sp.…”
Section: Biodegradationmentioning
confidence: 99%
“…Recently, Tortella et al [91] demonstrated the increased degradation of the insecticide chlorpyrifos using Applied and Environmental Soil Science 7 an agricultural biobed system biostimulated with inorganic fertilizer (NPK). In yet another study, McGhee and Burns [92] reported the significant increase in degradation of herbicides 2,4-D and 4-chloro-2-methylphenoxyacetic acid (MCPA) following the addition of a combined NPK fertilizer.…”
Section: Biostimulation: Field-scale Feasibilitymentioning
confidence: 99%
“…Finally, the biological activity in the biomixture increased due to the presence of NPK in all the evaluated concentrations. In conclusion, the results demonstrated that the biomix prepared with an Andisol and biostimulated with NPK nutrient can be recommended in biobeds as a viable alternative to chlorpyrifos dissipation, thereby avoiding the likelihood of soil and water contamination (Tortella et al 2010 ). By contrast, and taking into account that biostimulation of organicpollutant-degrading microorganisms by adding volatile organic compounds such as terpenes has been used to increase pollutant biodegradation in contaminated soils (Bento et al 2005 ;Tyagi et al 2011 ;Dudášová et al 2012 ), Tortella et al ( 2013d ) studied the effect of the terpenes α-pinene, eucalyptol, and limonene, individually and as mixtures, on atrazine biodegradation and on biological activity in a biobed biomixture.…”
Section: Pesticide Degradation In Biobeds: Studies At Laboratory Scalementioning
confidence: 94%
“…As has been observed, pesticide degradation in biobeds can be limited or improved by several factors. Biostimulation of the indigenous microorganisms through the addition of nutrients is an important aspect to consider because the enrichment of the indigenous microbial populations is the most widely used tool in a bioremediation procedure (Tortella et al 2010 ). In this context and in order to ascertain the effect of biomixture stimulation, Tortella et al ( 2010 ) evaluated the degradation of chlorpyrifos (160 a.i.…”
Section: Pesticide Degradation In Biobeds: Studies At Laboratory Scalementioning
confidence: 99%
See 1 more Smart Citation